Development of accounting systems: improvement of effectiveness in microenterprises (Revista de Investigaciones Universidad del Quindío, 2022)
Companies are for-profit organizations, which, through the commercialization of goods and services, seek to have a better economic level, offering the need a great diversity of products, with which they satisfy social needs. These entities have a classification which is established by the number of individuals within it, to which the present research work will focus on microenterprises, organizations that are taking great importance in economic development worldwide, this work will be addressed through accounting systems as these improve effectiveness within the microenterprise, aiming to describe in a clear and argumentative way, the importance of accounting systems in companies and above all the great impact it has on even smaller ones.
Keywords: companies; information; decision making; organization; accounting systems